2001
DOI: 10.1111/j.1553-2712.2001.tb02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Correlation between Diffusion of Loxosceles reclusa Venom and Extent of Dermal Inflammation

Abstract: Abstract. Objectives: Envenomation by Loxosceles species (brown recluse) spiders results in large dermal inflammatory lesions. Venom-induced dermal inflammation occurs indirectly via soluble mediators of inflammation. This study aimed to explore whether the anatomic extent of dermonecrotic arachnidism is due to the cascade of soluble proinflammatory mediators elicited by venom deposited at the bite site, or due to diffusion of the venom per se. Methods: Three New Zealand white rabbits received intradermal L. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…21 Our Loxosceles species ELISA assay was specific for Loxosceles species venom when relevant amounts of venom (likely to be recovered from a dermal lesion) were tested. We have observed that venom amounts of less than 40 ng per 100 μL of homogenized tissue are detected from dermal punch biopsy specimens obtained 24 hours after Loxosceles species venom inoculation into rabbit dermis 19,20 and in 1 confirmed case of L arizonica human envenomation. 24 A sensitive and specific Loxosceles species venom assay is clinically needed.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…21 Our Loxosceles species ELISA assay was specific for Loxosceles species venom when relevant amounts of venom (likely to be recovered from a dermal lesion) were tested. We have observed that venom amounts of less than 40 ng per 100 μL of homogenized tissue are detected from dermal punch biopsy specimens obtained 24 hours after Loxosceles species venom inoculation into rabbit dermis 19,20 and in 1 confirmed case of L arizonica human envenomation. 24 A sensitive and specific Loxosceles species venom assay is clinically needed.…”
Section: Discussionmentioning
confidence: 95%
“…The approximate amount of venom deposited from a single spider bite is 2,000 ng (personal communication, Charles Kristensen, Spider Pharm Inc, Yarnell, AZ, April 2001), whereas 40 ng is the maximum amount of Loxosceles species venom we recover from 100 μL of homogenized rabbit dermis 24 hours after simulated spider bites. 19,20 Similar amounts of L reclusa venom and bovine serum albumin served as positive and negative controls, respectively. Study and control preparations were coded and placed in Eppendorf tubes of identical appearance before performing the assay to ensure blinding of the investigator performing the ELISA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations